2006
DOI: 10.1159/000091414
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Soluble Adhesion Molecule Levels in Coronary Artery Ectasia

Abstract: Background:Coronary artery ectasia (CAE) is defined as localized or diffuse dilatation of the coronary arteries. There are scarce data about the role of inflammation in CAE. In the present study, the plasma soluble adhesion molecules intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1) levels in CAE were investigated. Methods: The study population (n = 67) consisted of four groups. Group 1: patients with normal coronary artery (NCA); group 2: patients with isolated ectasia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
0
21
0
2
Order By: Relevance
“…A significant positive correlation between the levels of these adhesion molecules and the length of vascular segments with ectasia was also found [47]. Higher levels of ICAM-1 and VCAM-1 were also noted in cases with a combination of ectasia and obstructive coronary artery disease [48].…”
Section: Role Of Adhesion Moleculesmentioning
confidence: 75%
“…A significant positive correlation between the levels of these adhesion molecules and the length of vascular segments with ectasia was also found [47]. Higher levels of ICAM-1 and VCAM-1 were also noted in cases with a combination of ectasia and obstructive coronary artery disease [48].…”
Section: Role Of Adhesion Moleculesmentioning
confidence: 75%
“…The inflammatory component has been reported in multiple papers. Among different inflammatory markers, there is an increased expression of different adhesion molecules, such as vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1) and E-selectin, which facilitate the attachment and transmigration of the neutrophils and mononuclear cells across the vascular endothelial layer [31,32]. These leukocytes initiate the inflammatory process that causes the characteristic destruction of the vascular media where smooth muscles are replaced by hyalinized collagen [30].…”
Section: Pathogenesismentioning
confidence: 99%
“…This study showed that CAE was associated with inflammatory response presented as elevated inflammatory cytokines and differential leukocytes. Yilmaz et al 39 found that patients with isolated CAE had raised levels of plasma soluble intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1) and E selectin in comparison with patients with obstructive CAD without CAE and control subjects with normal coronary arteries, suggesting the presence of a more severe and extensive chronic inflammation in the coronary circulation in these patients.…”
Section: Discussionmentioning
confidence: 99%